Effect of Virgin Coconut Oil Supplementation on Immune Function in a Rat Model of Physical Exercise - Fajar Apollo Sinaga; Rika Nailuvar Sinaga; Alin Anggreni Ginting; Ayu Elvana (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Physical exercise can induce physiological stress that triggers inflammatory responses, marked by increased levels of proinflammatory cytokines and acute-phase proteins. Virgin Coconut Oil (VCO) contains medium-chain fatty acids that are known to possess anti-inflammatory and immunomodulatory properties, which may help regulate immune responses caused by physical activity. This study aimed to evaluate the effect of VCO supplementation on immune function by examining serum levels of Interleukin-6 (IL-6), Tumor Necrosis Factor-α (TNF-α), and C-Reactive Protein (CRP) in a rat model subjected to physical exercise. An experimental approach was conducted using rats divided into four groups, consisting of a control group and several VCO-treated groups undergoing physical exercise. VCO was administered orally at varying doses throughout the exercise intervention period. At the end of the treatment, blood samples were collected, and serum concentrations of IL-6, TNF-α, and CRP were analyzed using immunoassay techniques. The data were evaluated descriptively to observe trends among the treatment groups. The findings demonstrated a consistent decrease in IL-6, TNF-α, and CRP levels in rats receiving VCO supplementation compared to the control group. The most pronounced reduction in all inflammatory markers was observed in the group receiving the highest dose of VCO, indicating a dose-dependent effect. These results suggest that VCO supplementation effectively attenuated exercise-induced inflammatory responses. Overall, VCO supplementation shows potential immunomodulatory and anti-inflammatory effects in rats exposed to physical exercise, as evidenced by reduced levels of IL-6, TNF-α, and CRP. VCO may therefore be considered a functional nutritional supplement to support immune balance during physical activity. However, further studies are needed to confirm these findings and to clarify the underlying biological mechanisms involved. Keywords: Virgin Coconut Oil, Physical Exercise, Immune Function, Inflammation, Interleukin-6, Tumor Necrosis Factor-α, C-Reactive Protein, Rat Model